2009
DOI: 10.1177/1403494809102778
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and self-reported and performance-based evaluation of physical function of elderly persons in rural Bangladesh

Abstract: Aim: To investigate the impact of nutritional status on self-reported as well as performance-based indicators of physical function in a rural elderly population in Bangladesh. Methods: A cross-sectional study conducted in Matlab, Bangladesh, included 457 randomly selected community-living elderly persons aged 60 years or more (60-92 years; 69 AE 7 years). Mobility, activities of daily living (ADL), performance tests, handgrip strength, the Mini Nutritional Assessment (MNA) and a structured questionnaire were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
35
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 20 publications
(29 reference statements)
7
35
2
2
Order By: Relevance
“…4,5 The functional limitations and disabilities are conditions prevalent in the elderly, [6][7][8][9] with implications for increased use of health services and institutionalization, creating a serious public health problem. 8,9 Some studies suggest that nutritional status is an indicator of health and an important factor associated with motor performance limitations 7,10,11 and disability relating to basic and instrumental activities of daily life (ADLs and IADLs). 11,14 However, there are disagreements about whether this association is due to the underweight and/ or overweight obesity status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The functional limitations and disabilities are conditions prevalent in the elderly, [6][7][8][9] with implications for increased use of health services and institutionalization, creating a serious public health problem. 8,9 Some studies suggest that nutritional status is an indicator of health and an important factor associated with motor performance limitations 7,10,11 and disability relating to basic and instrumental activities of daily life (ADLs and IADLs). 11,14 However, there are disagreements about whether this association is due to the underweight and/ or overweight obesity status.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Some studies suggest that nutritional status is an indicator of health and an important factor associated with motor performance limitations 7,10,11 and disability relating to basic and instrumental activities of daily life (ADLs and IADLs). 11,14 However, there are disagreements about whether this association is due to the underweight and/ or overweight obesity status.…”
Section: Introductionmentioning
confidence: 99%
“…Ruiz-López et al (30) observed a correlation between the MNA score and the mobility of institutionalised elderly women rated by the Katz score; and Chevalier et al (11) observed that malnourishment was correlated with poor physical performance (gait speed) in elderly patients undergoing ambulatory rehabilitation. Poor ADL and IADL status has been found to be correlated with poor nutritional status rated with the MNA in community-living (23) , institutionalised (6,31) and hospitalised elderly (32) . In several studies involving hospitalised or institutionalised elderly, the MNA has also been observed to have a functional status-predictive ability (7,23,24,33) .…”
Section: Predicting Functional Dependency and Declinementioning
confidence: 99%
“…Poor ADL and IADL status has been found to be correlated with poor nutritional status rated with the MNA in community-living (23) , institutionalised (6,31) and hospitalised elderly (32) . In several studies involving hospitalised or institutionalised elderly, the MNA has also been observed to have a functional status-predictive ability (7,23,24,33) . Cereda et al (33) have shown that the MNA is suitable for grading functional status of institutionalised elderly.…”
Section: Predicting Functional Dependency and Declinementioning
confidence: 99%
See 1 more Smart Citation